PENGARUH KOMPENSASI, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. ANUGERAH TANJUNG GUMUKMAS KABUPATEN JEMBER - Bagas Yuszulfikar; Sudarsih Sudarsih; Nurhayati Nurhayati (VALUE: Journal of Business Studies, 2022)
The achievement of the company's objectives is determined by the quality of human resources in the company. If in a company there is a good quality of human resources, then the process of achieving the company's goals will be easier to achieve. The creation of good employee performance can make it easier for the company to achieve its goals. There are several things that can be done, including the procurement of good compensation to employees, the discipline of employees in accordance with the provisions, and the cultural climate of the organization in accordance with the circumstances of its employees. This research has free variables such as compensation, work discipline, and organizational culture. While the variables tied in this study are employee performance. The purpose of this study is to test and analyze the effect of compensation, work discipline, and organizational culture on the performance of PT employees. Tanjung Gumukmas Award in Jember Regency. The population in this study was 47 employees, sampling techniques used are total sampling, i.e. the entire population is used as a research sample. The data analysis method used is multiple linear regression analysis. The results showed that compensation, work discipline, and organizational culture had a significant impact on the performance of employees. PT. Anugerah Tanjung Gumukmas in Jember Regency